Frequency of New Onset Atrial Fibrillation in Patients Presenting with ST-Segment Elevation Myocardial Infarction - Zahid Hussain, Iftikhar Ahmed, Faiza Alam, Attiya Mustafa, Naveed Ahmed, Abdul Manaf (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To study the magnitude of atrial fibrillation in patients with ST segment elevation myocardial infarction. Study Design: Prospective analytic cross-sectional study. Place and duration of study: Department of Cardiology of a Tertiary Cardiac Care Center of Pakistan from 1st June 2022 to 30th November 2022. Methodology: Two hundred and thirty-six patients were selected through non-probability, consecutive sampling technique. Patients were divided into Group 1 who did not develop AF while group 2 included the new cases of AF during in-hospital stay for STEMI. All patients underwent clinical examinations, echocardiography, angiography and percutaneous coronary intervention. Results: Forty five cases with an average age of 71±14 years developed atrial fibrillation. Female population 25(60%) was at higher risk than male 17(40%). In AF group, 22(53.3%) cases of dyslipidemia, 11(26.1%) cases of chronic renal disease, 4(8.8%) cases of prior myocardial infarction, 14(33.3%) cases of diabetes and a single case (2.2%) of implantable cardiac-defibrillator were observed when compared with the non-AF group. Practical Implication: In-hospital complications are also highly associated with AF which may result in high Incidents of mortality. Conclusion: Aging, comorbidities and inferior wall MI are the independent predictors of AF. In-hospital complications are associated with AF which may result in high incidents of mortality. Early diagnosis of STEMI patients with a high risk of developing AF is necessary to reduce the morbidity and mortality. Keywords: Atrial fibrillation, ST-segment elevation, Myocardial infarction